ADOPSI INOVASI LOKAL BUDIDAYA KENTANG (Studi Kasus Di Desa Karamatwangi Kecamatan Cisurupan Kabupaten Garut) - Shalsabilah Ferbiansari; Ahmad Choibar Tridakusumah (Universitas Galuh, 2023)
This research was carried out based on the emergence of common problems that occur on the land or other technical problems due to the lack of information obtained by rural farmers. The objectives of this study are Knowing the characteristics of potato cultivation, Describe local innovations in potato cultivation, and Analyze the adoption of local innovations in potato cultivation in Karamatwangi Village, Cisurupan, Garut Regency. Informants were selected using the Snowball sampling technique. The research method used is qualitative with a case study approach with data collection techniques of observation, documentation and in-depth interviews with questionnaire instruments. Data analysis used descriptive analysis. The results showed potato farmers in Karamatwangi Village have local innovations in their cultivation processes such as the use of natural ingredients as land fertilizers and pest control drugs, maintenance of superior seeds, selection of planting patterns that are in accordance with land conditions in Karamatwangi Village, and others. Potato farmers in Karamatwangi Village have adopted local innovations well. The effect of the adoption of local innovation is the emphasis on the cost of production facilities.